Umbilical Cord-Derived Wharton's Jelly for Regenerative Medicine Applications: A Systematic Review - Benjamin J. Main; Nicola Maffulli; Josiah A. Valk; Hugo C. Rodriguez; Manu Gupta; Saadiq F. El-Amin; Ashim Gupta (MDPI AG, 2021)
Musculoskeletal ailments affect millions of people around the world and place a high burden on healthcare. Traditional treatment modalities are limited and do not address underlying pathologies. Mesenchymal stem cells (MSCs) have emerged as an exciting therapeutic alternative and Wharton's jelly-derived mesenchymal stem cells (WJSCs) are some of these. This review reports the clinical and functional outcomes of the applications of WJSCs in orthopedic surgery. A systematic review was conducted utilizing the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. The studies that used culture-expanded, mesenchymal stem or stromal cells, MSCs and/or connective tissues procured from Wharton's jelly (WJ), from January 2010 to October 2021, were included. Conventional non-operative therapies and placebos were used as comparisons. Six studies that directly discussed WJSCs use in an animal model or the basic scientific testing using an injury model were identified. Five publications studied cartilage injury, three studied degenerative disc disease, one was related to osteoarthritis, and one was related to osteochondral defects. The results of these studies suggested the benefits of WJSCs in the management of these orthopedic pathologies. To adequately assess the safety and efficacy of WJSCs in orthopedic surgery, further randomized controlled clinical studies are necessary.